Amifostine can differentially modulate DNA double-strand breaks and apoptosis induced by idarubicin in normal and cancer cells - Wozniak, K.; Gloc, E.; Morawiec, Z.; Blasiak, J. (Experimental Oncology, 2008)
We have previously shown that amifostine differentially modulated the DNA-damaging action of idarubicin in normal and cancer cells and that the presence of p53 protein and oncogenic tyrosine kinases might play a role in this diversity. Aim: To investigate further this effect we have studied the influence of amifostine on idarubicin-induced DNA double-strand breaks (DSBs) and apoptosis. Methods: We employed pulse-field gel electrophoresis () for the detection of DSBs and assessment of their repair in human normal lymphocytes and chronic myelogenous leukaemia K562 cells lacking p53 activity and expressing the BCR/ABL tyrosine kinase. Apoptosis was evaluated by caspase-3 activity assay assisted by the alkaline comet assay and DAPI staining. Results: Idarubicin induced DSBs in a dose-independent manner in normal and cancer cells. Both types of the cells did not repair these lesions in 120 min and amifostine differentially modulated their level — decreased it in the lymphocytes and increased in K562 cells. In contrast to control cells, amifostine potentated apoptotic DNA fragmentation, chromatin condensation and the activity of caspase-3 in leukaemia cells. Conclusion: Amifostine can differentially modulate DSBs and apoptosis induced by idarubicin in normal and cancer cells. It can protect normal cells against drug-induced DNA damage and it can potentate the action of the drug in leukaemic cells. Further studies on link between amifostine-induced modulation of DSBs and apoptosis of cancer cells will bring a deeper insight into molecular mechanism of amifostine action. Ранее нами было показано, что амифостин дифференциально модулирует ДНК-повреждающее действие идарубицина в нормальных и злокачественных клетках, и что наличие белка р53 и онкогенных тирозин киназ может иметь значение для этих различий. Цель: изучить влияние амифостина на идарубицин-опосредованные двухнитевые разрывы ДНК (DSBs) и апоптоз. Методы: мы применили гель-электрофорез в пульсирующем поле (PFGE) для выявления DSBs и изучения их репарации в нормальных лимфоцитах человека и клетках K562 хронической миелоидной лейкемии, у которых р53 неактивен и экспрессирована BCR/ABL-тирозин киназа. Апоптоз оценивали с помощью реактивов для выявления активности каспазы-3, проведения щелочного гель-электрофореза одиночных клеток и DAPI-окрашивания. Результаты: идарубицин вызывает образование DSBs в нормальных и злокачественных клетках независимо от дозы. Оба типа клеток не репарировали эти повреждения за 120 мин, при этом амифостин дифференциально молулировал уровень DSBs — уменьшал в лимфоцитах и увеличивал в K562-клетках. В отличие от контрольных клеток амифостин потенциировал апоптическую фрагментацию ДНК, конденсацию хроматина и активность каспазы-3 в лейкемических клетках. Выводы: амифостин может дифференциально модулировать DSBs и апоптоз, вызванные идарубицином в нормальных и злокачественных клетках. Он может защитить нормальные клетки от повреждения ДНК, вызванного химиопрепаратом, и в то же время потенциировать действие препарата на лейкемические клетки. Дальнейшие исследования связи между вызванной амифостином модуляцией DSBs и апоптоза опухолевых клеток позволит лучше понять молекулярные механизмы действия амифостина.